Behavioral alterations induced by post-weaning isolation rearing of rats are accompanied by reduced VGF/BDNF/TrkB signaling in the hippocampus. (October 2019) - Chmelova, M.; Balagova, L.; Marko, M.; Vrankova, S.; Cebova, M.; Jezova, D.; Riecansky, I.; Hlavacova, N.
Abstract: Post-weaning social isolation has been shown to be a relevant animal model for studying the mechanisms underlying psychopathological states induced by early-life stressful experiences. Besides extensively studied brain-derived neurotrophic factor (BDNF) and tyrosine receptor kinase B (TrkB) receptor, increasing attention is being given to a neuropeptide precursor VGF (non-acronymic). Several lines of evidence indicate an interplay between the neurotrophins and nitric oxide signaling. This study investigated the long-term consequences of post-weaning social isolation on behavior, VGF/BDNF/TrkB pathway and two isoforms of nitric oxide synthase (NOS) in the hippocampus and examined whether these effects were sex-specific. Male and female Sprague-Dawley rats were reared either in social isolation or social groups from postnatal day 21 for 9 weeks (n = 12–15/group and sex). Post-weaning social isolation induced impairments in sensorimotor gating and increased anxiety-like behavior in rats of both sexes. These behavioral alterations were accompanied by attenuated gene expression of VGF and TrkB receptor in the hippocampus. Isolation-induced reduction in VGF gene expression was more evident in male isolates. Similar changes were found in neuronal NOS (nNOS) gene expression with reduced mRNA levels in male isolates. Gene expression of BDNF and inducible NOS was not influenced by isolation rearing or sex. In addition, sex-specific patterns of VGF and nNOS gene expression in the hippocampus with higher mRNA levels in males than in females were revealed. The present study demonstrates a relationship between nNOS, VGF, BDNF, and TrkB confirming a link between nitric oxide and neurotrophins signaling pathways. Our findings indicate that long-term post-weaning social isolation alters signaling via VGF/BDNF/TrkB and nNOS that could interfere with neurodevelopmental processes which may contribute to pathological behavioral symptoms in adulthood. Future studies are needed to support this suggestion since the direct mechanistic link has not been approached in this study. Graphical abstract: Image 1 Highlights: Post-weaning social isolation reduces signaling via VGF/BDNF/TrkB pathway. Isolation rearing reduces hippocampal neuronal nitric oxide synthase (nNOS) mRNA levels. Isolation-induced reduction in VGF and nNOS mRNA levels is more evident in male isolates. Sex-specific patterns of VGF and nNOS gene expression do exist. Isolation rearing induces deficit in prepulse inhibition and anxious phenotype.